Attenuating Listeria monocytogenes Virulence by Targeting the Regulatory Protein PrfA. Issue 3 (17th March 2016) - Good, James A.D.; Andersson, Christopher; Hansen, Sabine; Wall, Jessica; Krishnan, K. Syam; Begum, Afshan; Grundström, Christin; Niemiec, Moritz S.; Vaitkevicius, Karolis; Chorell, Erik; Wittung-Stafshede, Pernilla; Sauer, Uwe H.; et al.
Summary: The transcriptional activator PrfA, a member of the Crp/Fnr family, controls the expression of some key virulence factors necessary for infection by the human bacterial pathogen Listeria monocytogenes . Phenotypic screening identified ring-fused 2-pyridone molecules that at low micromolar concentrations attenuate L. monocytogenes cellular uptake by reducing the expression of virulence genes. These inhibitors bind the transcriptional regulator PrfA and decrease its affinity for the consensus DNA-binding site. Structural characterization of this interaction revealed that one of the ring-fused 2-pyridones, compound1, binds at two separate sites on the protein: one within a hydrophobic pocket or tunnel, located between the C- and N-terminal domains of PrfA, and the second in the vicinity of the DNA-binding helix-turn-helix motif. At both sites the compound interacts with residues important for PrfA activation and helix-turn-helix formation. Ring-fused 2-pyridones represent a new class of chemical probes for studying virulence in L. monocytogenes . Graphical Abstract: Highlights: Inhibitors of L. monocytogenes infectivity reduce virulence gene expression Binding of inhibitor to the PrfA regulator reduces affinity for its DNA motif First crystal structure of a Crp family regulator with an inhibitor Provides rationale for screening with Crp family transcriptional regulators Abstract : In this study, Good et al. identify ring-fused 2-pyridones which attenuate Listeria monocytogenes infectivity and reduce the expression of key virulence genes by binding to the central virulence regulator PrfA.